Potential Region Factors That Affect The Ratio Of Muzzaki-Mustahiq: A Solution To Reduce Poverty Case In Indonesia - S.ST., Rara Karina; S.ST, Amrin Barata; S.ST., Nanda Adi Pradana (Universiti Sains Islam Malaysia, 2024)
Indonesia as the largest country with islamic region continues to develop conventional economics and Islamic economics. The development of the two makes a lot of thought to overcome poverty in Indonesia. Islam has zakat as the solution of poverty problem. However, the zakat records in Indonesia does not reach one percent from the potential that has been predicted. Whereas, knowledge of records Muzakki and Mustahiq is very important to optimize the zakat distribution. On the other hand, optimization potential of zakat also requires knowledge of regional potential. This study aims to get an overview of characteristics and distribution of Muzakki Mustahiq in Indonesia and also to determine the impact of the regional potential to the Muzakki Mustahiq households ratio in the province and districts levels in Indonesia. The analytical method used are cluster analysis and multiple linear regression analysis. The result of study in provincial level shows the variables of the percentage of villages with the largest income of population comes from processing industry, percentage of villages that have the widest road in the form of asphalt or paved road, percentage of vilages that have Village Unit Cooperatives, percentages of vilages that have Rural Banks has the effect to the Muzakki Mustahiq households ratio. In the district level, the variable that have effect to the Muzakki Mustahiq households ratio is only percentage of village that have Rural Banks.